Opakované plicní resekce v chirurgii plicních metastáz - Čapov, I; Doležel, J; Vlček, P; Jedlička, V; Peštál, A; Veverková, L; Veselý, M; Chovanec, Z; Benej, M (Rozhledy v chirurgii, 2013)
INTRODUCTION: Repeated pulmonary resections are predominantly used in sarcomas, colorectal cancer, Grawitz tumours, and at a young age in general. Patients with the recurrence of pulmonary metastases within a period of six months have a poor prognosis. MATERIAL AND METHODS: During the period from I/1997 to XII/2011, a total of 165 operations were performed in 149 patients. 11patients had multiple pulmonary resections. According to histological origin, sarcomas were found in 6 cases, Grawitz tumours in 2 cases, Schwannoma malignum in 1 case and laryngeal carcinoma in 1 case. There was synovialosarcoma, osteosarcoma, rhabdomyosarcoma, alveolar sarcoma and uterine sarcoma in the group of sarcomas. RESULTS: In our retrospective study, the most commonly used approach was muscle-sparing vertical thoracotomy in 14 patients, posterolateral thoracotomy in 8 patients, VATS in 3 patients and clamshell thoracotomy in 3 patients. We performed 22 extraanatomic resections - of which 3 times VATS, 6 times lobectomy (of which 1 completion pneumonectomy). We observed complications in 6 cases (small air leak in 3 patients, wound infection in 3 patients) in the postoperative period. No rethoracotomy for complications was needed, lethality was 0. The overall 5-year survival that we observed was 45.4%. CONCLUSION: Surgery is an integral part of complex oncological care. What is extremely important is strict selection of patients eligible for surgery for repeated resections and, of course, an experienced team of thoracic surgeons, but also other physicians. When performed by experienced specialists, surgical treatment of lung metastases is a safe and very useful procedure.
Keywords: nádory plic; Pneumonectomy; Lung Neoplasms; Humans; lidé středního věku; Female; Aged; dospělí; senioři; lidé; reoperace; pneumektomie; Adult; ženské pohlaví; lung metastases - repeated lung resection.; Middle Aged; Retrospective Studies; prognóza; retrospektivní studie; lokální recidiva nádoru; míra přežití; Neoplasm Recurrence, Local; Reoperation; Prognosis; Survival Rate